Photocatalytic Degradation of Malachite Green by NiAl-LDH Intercalated Polyoxometalate Compound - Yulizah Hanifah; Mardiyanto Mardiyanto; Risfidian Mohadi; Aldes Lesbani (Masyarakat Katalis Indonesia - Indonesian Catalyst Society (MKICS), 2022)
Composites based on layered double hydroxide with polyoxometalate K3[-PW12O40] and K4[-SiW12O40] were synthesized to form NiAl-[SiW12O40] and NiAl-[PW12O40]. The materials were characterized by XRD, FTIR, SEM, and UV-DRS and were then applied as a photocatalyst to degrade MG. The effects of catalyst loading, pH value, and contact times on photodegradation performance were carried out in this study. The results indicated that NiAl-LDH was successfully synthesized by showing the peak diffractions at angles 11.63°, 23.13°, and 35.16°. Both kinds of attained NiAl-[SiW12O40] and NiAl-[PW12O40] had typical structures of LDH that were proved by appearing diffraction at 2θ angles 10.76°, 26.59°, 30.8°, and 63.11° for NiAl-[PW12O40] and at 2θ angles 8.26°, 11.34°, 29°, and 35.1° for NiAl-[SiW12O40]. The materials used for the fifth regeneration were characterized by FTIR, which still presents characteristics of LDH structure. The photocatalyst was applied for the first time to degrade MG. The decrease of band gap on NiAl pristine than LDH composite from 4.76 eV to 3.22 eV for NiAl-[SiW12O40] and 3.78 eV for NiAl-[PW12O40] respectively, was presented by DR-UV analysis. LDH composite shows improved degradation photocatalytic performance in comparison with LDH pristine. It was present by the %degradation MG performances were 68.94% for NiAl LDH, 84.51% for NiAl-[PW12O40]), and 88.91% for NiAl-[SiW12O40]. The degradation percentage indicates that the LDH-polyoxometalate composite has succeeded in increasing the ability of photodegradation catalytic and the regeneration ability of LDH pristine. Copyright © 2022 by Authors, Published by BCREC Group. This is an open access article under the CC BY-SA License (https://creativecommons.org/licenses/by-sa/4.0).